1987
DOI: 10.1002/food.19870310103
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an inhibitor of monoaminooxidase (nialamide) on the absorption and retention of nitrogen in adult rats

Abstract: A study was made on adult rats (170 g) of the effect of nialamide (20 mg/100 g of diet), an inhibitor of monoaminooxidase, administered for 15 or 30 days (short or long-term, respectively), with food intake controlled (pair fed), on the absorption and retention of nitrogen, and on the nitrogen content in the liver, the gastronemio and longissimus dorsi muscles and in the small intestine. Nialamide administered for a time which can be considered prolonged (30 days) negatively affects absorption of alimentary pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…An explanation for this effect may be deduced from the results of Youdim et al (1980), who found a reduction in the activity of monoaminoxidase (MAO) in Fe-deficient rats, and of Mackler, Person, Miller, Inamdar, & Finch (1978) who reported a low level of aldehyde oxidase activity in Fe-deficient rats. These enzymatic changes produce an increase in the endogenous levels of circulating catecholamines, which are known to increase the release rate of adrenocorticotrophic hormone, which in turn increases the production of glucocorticoids (Barrionuevo, Reche, Campos, & Mataix, 1987;.…”
Section: Article In Pressmentioning
confidence: 99%
“…An explanation for this effect may be deduced from the results of Youdim et al (1980), who found a reduction in the activity of monoaminoxidase (MAO) in Fe-deficient rats, and of Mackler, Person, Miller, Inamdar, & Finch (1978) who reported a low level of aldehyde oxidase activity in Fe-deficient rats. These enzymatic changes produce an increase in the endogenous levels of circulating catecholamines, which are known to increase the release rate of adrenocorticotrophic hormone, which in turn increases the production of glucocorticoids (Barrionuevo, Reche, Campos, & Mataix, 1987;.…”
Section: Article In Pressmentioning
confidence: 99%